The effect of economic growth, measure of industrialization, credit access, energy import dependency, and oil price on renewable energy production in the five biggest renewable energy producing countries in Southeast Asia - Domingo, Miguel John M. (Animo Repository, 2021)
Energy is seen as a necessary resource for economic progress, with policymakers continuously looking for sustainable solutions to increasing energy demand. Renewable energy has been recognized as a sustainable solution to energy security for its ability to ensure energy demand and lessen environmental degradation. Vietnam, Thailand, Indonesia, Malaysia, and the Philippines are the five biggest renewable energy producing countries in Southeast Asia, who are still looking to increase renewable energy production. The capital-intensive nature of renewable energy signifies the need to look at economic and technical factors. The study looks into the causal effects of economic growth, measure of industrialization, credit access, energy import dependency, and oil price on renewable energy production in these five countries using panel data in the years 1996 to 2018. The tests of assumptions have found that multicollinearity was not a problem, while correcting for cross-sectional dependence, heteroskedasticity, and autocorrelation. The Fixed Effects (FE) model was found to be the most suitable for the study. The results of the study found that the measure of industrialization, or the variable ratio of net manufacturing output to gross domestic product, and credit access, or the variable lending interest rates, had the most impact on renewable energy production. The study recommends the implementation of policies that ease the access to capital, as it is the most applicable to the five countries and will have the greatest impact on increasing renewable energy production. Keywords: ASEAN, Renewable Energy, Panel Regression, Government Policy, Renewable Energy Production JEL Classification: O32, Q02, Q28, Q42, Q43, Q48